The domestication of the African Union model law on medical products regulation: Perceived benefits, enabling factors, and challenges - Ncube, Bakani Mark; Dube, Admire; Ward, Kim (Frontiers in Medicine, 2023)
Introduction: In 2016, the African Union (AU) Model Law on Medical Products Regulation was endorsed by AU Heads of State and Government. The aims of the legislation include harmonisation of regulatory systems, increasing collaboration across countries, and providing a conducive regulatory environment for medical product/health technology development and scale-up. A target was set to have at least 25 African countries domesticating the model law by 2020. However, this target has not yet been met. This research aimed to apply the Consolidated Framework for Implementation Research (CFIR) in analysing the rationale, perceived benefits, enabling factors and challenges of AU Model Law domestication/implementation by AU Member States. Methods: This study was a qualitative, cross-sectional, census survey of the national medicines regulatory authorities (NRAs) of Anglophone and Francophone AU Member States. The heads of NRAs and a senior competent person were contacted to complete self-administered questionnaires. Results: The perceived benefits of model law implementation include enabling the establishment of an NRA, improving NRA governance and decision-making autonomy, strengthening the institutional framework, having streamlined activities which attract support from donors, as well as enabling harmonisation, reliance, and mutual recognition mechanisms. The factors enabling domestication and implementation are the presence of political will, leadership, and advocates, facilitators or champions for the cause. Additionally, participation in regulatory harmonisation initiatives and the desire to have legal provisions at the national level that allow for regional harmonisation and international collaboration are enabling factors. The challenges encountered in the process of domesticating and implementing the model law are the lack of human and financial resources, competing priorities at the national level, overlapping roles of government institutions, and the process of amending/repealing laws being slow and lengthy. Conclusion: This study has enabled an improved understanding of the AU Model Law process, the perceived benefits of its domestication, and the enabling factors for its adoption from the perspective of African NRAs. NRAs have also highlighted the challenges encountered in the process. Addressing these challenges will result in a harmonised legal environment for medicines regulation in Africa and be an important enabler for the effective operation of the African Medicines Agency.